KAJIAN YURIDIS PERALIHAN HAK ATAS TANAH WARISAN YANG SEDANG DIBEBANI HAK TANGGUNGAN - JULIA FRANCISKA (PREMISE LAW JURNAL, 2014)
ABSTRACT To provide legal certainty on the rights to land for all of the people of Indonesia, the government will implement land registration in all territory of the Republic of Indonesia. The right to land is the right giving an autorithy to the right holder to use or take advantage of the land he/she legally owns whether it is collateralized, shifted or transferred. The result of this study showed that the transfer of the right to inherited land was the transfer of right because of law, therefore, even though it is still in the imposition of mortgage, the right to land can still be transferred. The inhibiting factor faced by the creditor realted to the transfer of the right to inherited land still imposed in the collateral right was the transfer the title to the heirs. Keywords: Transfer, Right to land, Inheritance, Collateral Right